Change management in business process modeling survey - Rajabi, B.A.; Lee, S.P. (2009)
Change management is very important to reduce risks and costs and maximizes the benefits of such major changes in business and information technology. Business Process Modeling (BPM) is the first and most important step in business process management lifecycle. BPM technology continues to face challenges in coping with dynamic business environments where requirements and goals are constantly changing at the execution time. In this paper a comparative study about the BPM languages and their runtime change management techniques will be provided and discussed.